Variation in Orgasm Occurrence by Sexual Orientation in a Sample of U.S. Singles. (18th August 2014) - Garcia, Justin R.; Lloyd, Elisabeth A.; Wallen, Kim; Fisher, Helen E.
Abstract Introduction Despite recent advances in understanding orgasm variation, little is known about ways in which sexual orientation is associated with men's and women's orgasm occurrence. Aim To assess orgasm occurrence during sexual activity across sexual orientation categories. Methods Data were collected by Internet questionnaire from 6, 151 men and women (ages 21–65+ years) as part of a nationally representative sample of single individuals in the United States. Analyses were restricted to a subsample of 2, 850 singles (1, 497 men, 1, 353 women) who had experienced sexual activity in the past 12 months. Main Outcome Measures Participants reported their sex/gender, self‐identified sexual orientation (heterosexual, gay/lesbian, bisexual), and what percentage of the time they experience orgasm when having sex with a familiar partner. Results Mean occurrence rate for experiencing orgasm during sexual activity with a familiar partner was 62.9% among single women and 85.1% among single men, which was significantly different (F1, 2848 = 370.6, P < 0.001, η2 = 0.12). For men, mean occurrence rate of orgasm did not vary by sexual orientation: heterosexual men 85.5%, gay men 84.7%, bisexual men 77.6% (F2, 1494 = 2.67, P = 0.07, η2 = 0.004). For women, however, mean occurrence rate of orgasm varied significantly by sexual orientation: heterosexual women 61.6%, lesbian women 74.7%, bisexual women 58.0% (F2, 1350 = 10.95, P < 0.001, η2 = 0.02). Lesbian women had a significantly higher probability of orgasm than did either heterosexual or bisexual women (P < 0.05). Conclusions Findings from this large dataset of U.S. singles suggest that women, regardless of sexual orientation, have less predictable, more varied orgasm experiences than do men and that for women, but not men, the likelihood of orgasm varies with sexual orientation. These findings demonstrate the need for further investigations into the comparative sexual experiences and sexual health outcomes of sexual minorities. Garcia JR, Lloyd EA, Wallen K, and Fisher HE. Variation in orgasm occurrence by sexual orientation in a sample of U.S. singles. J Sex Med 2014;11:2645–2652.